Strangers & pilgrims : female preaching in America, 1740-1845 - Brekus, Catherine A. (Gender & American culture., 1998)
"Catherine Brekus tells the story of several generations of women - both white and African American - who struggled to forge an enduring tradition of female religious leadership in colonial and antebellum America. Piecing together evidence from a wide range of sources, including religious magazines and newspapers, clergymen's autobiographies, church records, and female preachers' own memoirs and letters, she examines the lives of more than a hundred female preachers who crisscrossed the country between 1740 and 1845." "Focusing on the lives of these forgotten women, Brekus explores the changing meaning of femininity after the American Revolution, the growth of religious freedom, the conservatism of evangelical revivals, the upheaval wrought by the market revolution, the popularity of apocalyptic beliefs, and the fragility of historical memory."--Jacket.